Analysis of Fast and Slow Acid Dissociation Equilibria of 3′,3″,5′,5″-Tetrabromophenolphthalein and Determination of Its Equilibrium Constants by Capillary Zone Electrophoresis - TAKAYANAGI, Toshio (Analytical Sciences, 2013)
Acid dissociation constants of 3′,3″,5′,5″-tetrabrompohenolphthalein (TBPP) were determined in an aqueous solution by capillary zone electrophoresis at an ionic strength of 0.01 mol/L. Two steps of the fast acid-dissociation equilibria including precipitable species of H2TBPP were analyzed at a weakly acidic pH region by using the change in effective electrophoretic mobility of TBPP with the pH of the separation buffer. On the other hand, an acid-dissociation reaction of TBPP at an alkaline pH region was reversible, but very slow to reach its equilibrium; the two TBPP species concerned with the equilibrium were detected as distinct signals in the electropherograms. After reaching its equilibrium, the acid-dissociation constant was determined with the signal height corresponding to its dianion form. Thus, three steps of the acid dissociation constants of TBPP were determined in an aqueous solution as pKa1 = 5.29 ± 0.06, pKa2 = 6.35 ± 0.02, and pKa3 = 11.03 ± 0.04.